Analisis Dampak Produk Pembiayaan Setifikasi Guru (SerGur) Terhadap Peningkatan Profit di Bank Pembiayaan Rakyat (BPR) Syariah Tanmiya Artha Kediri - Moch. Uzeir Mustaqfirin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
This study aims to determine the products provided by BPRS Tanmiya Artha Kediri and the influence of Teacher Certification financing products on increasing the profit of BPRS Tanmiya Artha Kediri. This research method uses a descriptive qualitative approach. The data used are primary data with data collection techniques using interviews, observations, and documentation. The conclusion of this study is that BPRS Tanmiya Artha has banking products including wadiah savings, mudlarabah savings, time deposit savings, murabahah financing (working capital financing, investment, consumption), multi-service financing (school fees, land rent, treatment, circumcision), mudlarabah financing, teacher certificationfinancing, receiving electricity, water, internet and telephone payment services. For teacher certification financing, it is one of the variants of BPRS Tanmiya Artha financing products with educator certificates owned by teacher certification customers as collateral or collateral. And the impact of SerGur financing on the profitability of Tanmiya Artha BPRS can be seen from the ROA, ROE and NPM of Tanmiya Artha BPRS in developing condition and good status. After the existence of new SerGur financing products, the profitability level of BPRS Tanmiya Artha increases every year.